2014
DOI: 10.1371/journal.pone.0114420
|View full text |Cite
|
Sign up to set email alerts
|

MiR-143 and MiR-145 Regulate IGF1R to Suppress Cell Proliferation in Colorectal Cancer

Abstract: Insulin-like growth factor 1 receptor (IGF1R) is a transmembrane receptor that is activated by insulin-like growth factor 1 (IGF-1) and by a related hormone called IGF-2. It belongs to the large class of tyrosine kinase receptors and plays an important role in colorectal cancer etiology and progression. In this study, we used bioinformatic analyses to search for miRNAs that potentially target IGF1R. We identified specific target sites for miR-143 and miR-145 (miR-143/145) in the 3′-untranslated region (3′-UTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…miR-143 and miR-145 target a large number of genes in various biological contexts including K-RAS and N-RAS (40,(45)(46)(47)(48)(49)(50)(51)(52)(53). To determine the mechanism through which miR-143/145 loss cooperates with pten deficiency to promote aggressive mammary tumors we performed the following analysis.…”
Section: Functional Cooperation Between Mir-143/145 and Pten Loss Promentioning
confidence: 99%
“…miR-143 and miR-145 target a large number of genes in various biological contexts including K-RAS and N-RAS (40,(45)(46)(47)(48)(49)(50)(51)(52)(53). To determine the mechanism through which miR-143/145 loss cooperates with pten deficiency to promote aggressive mammary tumors we performed the following analysis.…”
Section: Functional Cooperation Between Mir-143/145 and Pten Loss Promentioning
confidence: 99%
“…Discussion miR-143 is located in the chromosome 5 with a mature length of 22 [10]. A previous study has revealed that miR-143 exhibited down-regulation in many cancers such as colorectal cancer [11], pancreatic cancer [12] and lung cancer [13] in which miR-143 acts as a tumor suppressor inhibiting cell proliferation and inducing tumor cell apoptosis thus hindering the development of cancer [10]. miR-143 was exploited in many cancers e.g.…”
Section: Resultsmentioning
confidence: 99%
“…lung cancer [14], gastric cancer [15], colorectal cancer [16], osteosarcoma [17], T-cell leukemia [18] and prostate cancer [19]. While some proposed the idea of a cancer suppression effect through mediators as IGF1 [11], matrix metalloprotease 13 [17] while others proposed the effect of miR-143 on ERK5 pathway increasing apoptosis [18,19] In the present study we found no correlation between miR-143 expression and occurrence of HCC in HCV infected patients, and this was in contrary to a recent study which showed that miR-143 was down-regulated in HCC patients [1].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, IGF1R has been regarded as a valuable therapeutic target, and IGF1R-antagonistic monoclonal antibodies have been raised against the activity of IGF1R [32]. Several miRNAs, such as miR-133, miR-143, miR-145, and miR-503 [33][34][35], have been shown the ability to target IGF1R gene expression in different tumors. Our results also found that IGF1R was a direct target of miR-182 by luciferase reporter assay, and IGF1R could be negatively regulated by miR-182.…”
Section: Discussionmentioning
confidence: 99%